Clinical effectiveness of cognitive behavioural therapy on alcohol-dependent patients: an observation with the WeChat platform - Jing Chen; Mincai Qian; Conghao Sun; Min Lin; Weili Tang (General Psychiatry)
Background With the continuous improvement of people’s material living standards, the consumption of alcoholic beverages is increasing. Alcohol dependence caused by alcohol addiction has become a widespread concern in society. As the brand-new medical and health model created by the modern biomedical technology revolution and the information technology revolution, mobile health has been used more and more widely in the field of medical health with the characteristics of convenience, rapidity and generalisability. With the general use of the social software WeChat, it is feasible to implement mobile health on the WeChat platform.Aim We aimed to explore the clinical effect of WeChat platform used in the cognitive behavioural therapy (CBT) on the maintenance period of alcohol dependence and addiction.Methods Seventy alcohol-dependent patients in the withdrawal maintenance stage admitted into our hospital were randomly divided into the CBT on WeChat platform group (the experiment group, n=35) and the general clinical treatment using sertraline group (the control group, n=35) with block randomisation grouping. They were evaluated with the Severity of Alcohol Dependence Questionnaire (SADQ-C) before the treatment, at the end of the fourth week, at the end of the eighth week and at the end of the twelfth week of treatment. In addition, Zung’s Self-Rating Anxiety Scale (SAS) and Self-Rating Depression Scale (SDS) were employed to evaluate the degree of anxiety and depression of the two groups.Results The SADQ-C, SAS and SDS scores of the two groups after treatment decreased markedly compared with those before treatments, and the differences were statistically significant. Between-group comparison: the SADQ-C scores of the experiment group at the end of the fourth, eighth and twelfth weeks were lower than those of the control group, and the difference was statistically significant, which indicated that the score reduction in the experiment group was larger than that in the control group. The SAS and SDS scores of the experiment group at these time points were not significantly different from those of the control group, which indicated that these two treatment methods were comparable in treating patients’ anxiety and depression.Conclusion The CBT intervention using WeChat may improve the subjectively reported severity of alcohol dependence of patients who had completed detoxification. It is conducive to prevention of relapse, and is convenient for patients. It is worthy of clinical application and further study.